LITERATURE REVIEW: PENGARUH SENAM OTAK TERHADAP PENINGKATAN MEMORI JANGKA PENDEK SISWA: LITERATURE REVIEW: PENGARUH SENAM OTAK TERHADAP PENINGKATAN MEMORI JANGKA PENDEK SISWA - safaatin, Siti; Wijaya, Arif; Roni, Faishol; Sugiarto, Kresna Bagus (LPPM STIKes Bahrul Ulum Jombang, 2021)
ABSTRACT Brain storming is the series of phsycal exercise which has an objective to stimulate or give a prickling the brain potensial. Brain storming exercise will extremely goad the body’s part movement, movement synchronize, learning process, and the daily adjustment for the kid. Brain storming is strongly sugest for the childerns that have less reading comprehension. By doing brain storming, the closure brain part to be open totally. of this literature review is restate the effect of brain storming to the student’s short-term memory. This literature review is held based on the issue, methodology, similarities and the intermediate research purposal. There are five research that using descriptive quantitative method. The population is total of the students, and the sample is the several student at the school. There is an effect in brain storming to the short term memory raising. This study give the alternative way to the parent and the teacher in giving the learning process stimulation and also fulfil the student’s needs, whether at home or at school. For the reviewer, hopfully can develope the movement as the variety of the brain sorming well, in collage student level, senility level, etc.